Ethnopedagogical Approaches in Art Education: The Role of Balahak Performance in Cultural Transmission in Siulak Mukai - Alrizka Hairi Dilfa; Wadiyo Wadiyo; Udi Utomo; Agus Cahyono; Kusrina Widjayantie; Dhani Windra Guspa (AL-ISHLAH: Jurnal Pendidikan, 2025)
Traditional performing arts play a vital role in transmitting cultural values across generations. In Siulak Mukai, Kerinci Regency, the Balahak performance serves not only as a festive tradition but also as a medium of cultural and character education. This study explores how Balahak functions as an ethnopedagogical tool within community-based art education. Using a qualitative case study approach, data were collected through participatory observation of Balahak performances, in-depth interviews with local artists, community leaders, and participants, and analysis of related documentation. Data were analyzed using the Miles and Huberman model, with triangulation techniques employed to ensure validity. Findings show that Balahak performances consist of three stages—preparation, core, and reflection—which facilitate cultural value transmission and skill regeneration. Elements such as music, poetry, symbolic roles, and inclusive participation enable informal learning rooted in local traditions. Community members of all ages engage actively, creating a dynamic space for intergenerational education.Balahak reflects key principles of ethnopedagogy by embedding cultural knowledge, social norms, and character values within an experiential and communal art form. Its structure supports cultural preservation and strengthens identity, making it a viable model for integrating indigenous knowledge into formal and non-formal art education.